2015
DOI: 10.1007/s00246-015-1296-0
|View full text |Cite
|
Sign up to set email alerts
|

Intra-procedural Bronchoscopy to Prevent Bronchial Compression During Pulmonary Artery Stent Angioplasty

Abstract: Background Stenosis of the pulmonary arteries frequently occurs during staged palliation of hypoplastic left heart syndrome and variants, often necessitating stent angioplasty. A complication of stent angioplasty is compression of the ipsilateral main-stem bronchus. Following such a case, we re-evaluated our approach to PA stent angioplasty in these patients. Methods The incident case is described. A retrospective observational study of children and adults with superior(SCPC) and/or total cavopulmonary conne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…We briefly entertained whether compliance testing with simultaneous bronchoscopy as described in other clinical scenarios was worthwhile. However, this maneuver requires crossing the PDA with a wire, which, in our experience, can result in profound cyanosis and hemodynamic instability, especially in patients in whom the PDA is tortuous and/or the sole source of pulmonary blood flow.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…We briefly entertained whether compliance testing with simultaneous bronchoscopy as described in other clinical scenarios was worthwhile. However, this maneuver requires crossing the PDA with a wire, which, in our experience, can result in profound cyanosis and hemodynamic instability, especially in patients in whom the PDA is tortuous and/or the sole source of pulmonary blood flow.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…[6] Intraprocedural bronchoscopy is useful during specific interventional cardiology procedures as well, to avoid airway complications. [78] Backer et al . highlighted the importance of intraoperative bronchoscopy to confirm the success of the innominate arteriopexy operation as well as suggested monitoring of the right radial artery pulse to identify and prevent stenosis of the innominate artery by the suspension maneuver.…”
Section: Discussionmentioning
confidence: 99%
“…Bronchoscopy during pediatric pulmonary artery stent placement to detect bronchial compression during test angioplasty (without stenting) may be useful to avoid possible airway complications of this procedure. 33 This paper reported that in one of seven cases the observed bronchial compression during test angioplasty was so severe that it was decided not to place a pulmonary artery stent. Similarly, bronchoscopy may be important for treatment decisions in children with absent pulmonary valve syndrome.…”
Section: Flexible Bronchoscopy: Therapeutic Applicationsmentioning
confidence: 99%